1997
DOI: 10.1002/(sici)1096-9861(19970908)385:4<491::aid-cne1>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometries of AMPA receptor subunit mRNAs in rat brain fall into discrete categories

Abstract: In situ hybridization was used to estimate the relative concentrations of mRNAs encoding different subunits (GluR1-4) of alpha-amino 3-hydroxy-5-methyl-4-isoxazolepropionate (AMPA)-type glutamate receptors in rat brain and to test the hypothesis that within-region expression profiles reflect a limited number of recurring patterns. Fractional subunit mRNA concentrations were calculated for 33 brain regions, and cluster analysis methods were applied to test for statistically meaningful groupings in the data. Fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 53 publications
(57 reference statements)
4
29
0
Order By: Relevance
“…As shown in Fig. 7A, the relative proportion of the different AMPA receptor subunits, from both adult and aged hippocampus, agree with that previously reported (33). As also shown, no gross changes with aging were detected.…”
Section: Resultssupporting
confidence: 92%
“…As shown in Fig. 7A, the relative proportion of the different AMPA receptor subunits, from both adult and aged hippocampus, agree with that previously reported (33). As also shown, no gross changes with aging were detected.…”
Section: Resultssupporting
confidence: 92%
“…In previous work we observed that AMPA receptor-mediated synaptic responses in the hippocampal CA1 pyramidal cells of global Gria1-knockout mice are preserved indicating that, for synaptic transmission, the missing GluA subunits can be substituted by other AMPA receptor subunits (Zamanillo et al, 1999). Dense expression of both Gria2 and Gria4 subunit mRNA and low Gria3 mRNA expression have been reported previously in the ascending raphe nuclei of the midbrain (Gold et al, 1997;Sato et al, 1993). Thus, we hypothesize the enhanced AMPA response observed in 5-HT neurons lacking GLUA1 is mediated by receptors composed of the remaining subunits, which effectively substitute for GLUA1.…”
Section: Mechanisms Underlying the Behavioral Phenotypesupporting
confidence: 67%
“…Gria1 mRNA has been demonstrated in most neuronal populations of the brain including the ascending raphe nuclei (Gold et al, 1997;Sato et al, 1993), but Gria1 mRNA or GLUA1 protein expression specifically in serotonergic neurons has not, as yet, been confirmed. Here we show that in control mice GLUA1 is present in the overwhelming majority of DRN and MRN neurons, which co-label for TPH2 (and hence are presumed to be 5-HT neurons).…”
Section: Evidence For a Selective Loss Of Glua1mentioning
confidence: 96%
“…1, 1998 (Hampson eta!., 1992;Petralia and Wenthold, 1992;Martin et a!., 1993;Baude et al, 1994;Bernard et al, 1997;Petralia et a!., 1997). These studies have revealed that in adult rat brain G1uR1-4 transcripts (mainly the flip variant) have a unique subunit-specific distribution (see Bahn and Wisden, 1997;Gold et a!., 1997). Hippocampal CAl -4 pyramidal cells and dentate gyrus granule cells express high levels of G1uR1 -3 mRNAs.…”
Section: Binding To Tissue Sectionsmentioning
confidence: 99%
“…AMPA receptor subunits G1uR1 -4 are differentially regulated during ontogeny, and in adult rat brain they have only partially overlapping distributions (Keinanen et al, 1990;Monyer et a!., 1991;Hampson et al, 1992;Petralia and Wenthold, 1992;Martin et al, 1993;Sato et a!., 1993;Baude et al, 1994;Bahn and Wisden, 1997;Bernard et al, 1997;Petralia eta!., 1997). The stoichiometries of AMPA receptor subunit mRNAs in rat brain suggest the existence of four classes of receptor complexes (Gold et a!., 1997). Kainate receptor gene expression in adult rat brain (G!uR5-7 and KA-1 and -2; Bahn et a!., 1994) differs from AIvIPA receptor expression in its distribution.…”
mentioning
confidence: 99%